A novel model to predict phase equilibrium state of hydrates from the relationship of gas solubility - Jiang, Jianbing; Jiang, Jianxun; Mao, Jinchen; Li, Dong; Liu, Tuanhui; Pan, Zhong (Frontiers in Energy Research, 2024)
The study of hydrate phase equilibrium is crucial for ensuring the safety of natural gas pipeline transportation and the process of hydrate recovery. While scientists typically focus on the chemical potential of hydrates, the role of gas solubility in hydrate phase equilibrium remains unclear, and this study fills this gap. This work investigated the solubility of gas at the equilibrium point of the hydrate phase through model calculations. Additionally, a new model of hydrate phase equilibrium is established based on the relationship between solubility. Firstly, a solubility model based on gas-liquid equilibrium theory showed higher prediction accuracy in comparison to the PR equation and Duan model and was then used to calculate gas solubility under hydrate phase equilibrium conditions. Afterwards, a novel model was developed to predict hydrate equilibrium state based on the relationship between gas solubility and hydrate phase equilibrium temperature, and it was further compared with the Chen–Guo model and CSMGem in terms of prediction accuracy under pure water and brine settings. The results showed: (a) The calculation deviation of the solubility model was 0.7–8.7% in pure water settings and 2.6–11.7% in brine settings; (b) A strong linear correlation between the phase equilibrium temperature of hydrates and gas solubility was also found; (c) This proposed model achieved over 10 times the accuracy of the Chen–Guo model and the CSMGem in predicting the phase equilibrium state of N2 and CO2 hydrates, and 3–10 times higher accuracy than that of the Chen–Guo model and CSMGem in brine. This work suggests that the gas solubility equilibrium theory can provide a more accurate prediction of hydrate states.